A Study of Helicobacter pylori pathogenesis in laboratory mouse - Maitham Ghaly Yousif; Jamal Kadhim (Al-Qadisiyah Journal of Pure Science, 2017)
Helicobacter pylori is considered one of the most etiology of active chronic gastritis, peptic ulcer, ulcer and inflammation of the duodenum, gastric cancer, and tumors associated with the mucous layer.Gastric biopsies were collected from(80)a condition subject to examination endoscoby (42 males and 38 females) with differenced ages, in Deywanyia Teaching Hospital for the period 25/10/2009 until 09/03/2010 diagnosed 77 (96%) condition. The biopsies were taken from each patient from the mucous layer of the gastric antrum to investigate the bacteria H. pylori used one to check urease rapid and the other to isolate the bacteria into the center of DENTâ€²S selective medium, which is the best center in the first isolation compared to other media. The study showed the efficiency of test urease rapid screening for bacteria, as it was able to prove the presence of bacteria in 43 (54%) biopsy tissue, while the isolation of bacteria from 18 (23%) condition mediated transplant bacterial and under conditions of low ventilation, isolates genetically has been typing using specialized primers to the detect gene that represents the gene UreaC and equal (820) base pairs was spectrum using technology which is the most quality and sensitivity is a technology interaction polymerase serial (PCR) Polymerase Chain Reaction, where the local strains which secrete urease were grown, then genetic material isolated and purified DNA was from it to use in the investigation of gene UreaC responsible for the secretion of urease. The identification was made by direct bacterial H. pylori from the saliva of patients where it was purification and extraction of genetic material the DNA of the bacteria without the development and use of primers, specialized gene target Urea C and after amplification of this gene identified in four cases only satisfactory.The Histopathological studies of H. pylori in laboratory animals (mice) BALb / C mice showed the emergence of changes in tissue degenerative severe included the appearance of infiltration of cells, inflammatory, including cells multiple nuclei (Polymorph nuclear cells) (PMNs), (Lymphocyte cells) and (Plasma cells) in the lamina propria layer mucosa and the gastric glands, as demonstrated by degeneration of water in the epithelial cells of the layer of mucus and gastric glands to the point of increasing the volume of glands Hypertrophy with a erosion in the surface layer of the part of the mucosa and a case of congestion of the blood vessels with a case of vaculation in a number of epithelial cells infectious diseases, as well as the third group show the state of cellular degeneration and the onset of ulceration in the stomach mucosa, compared with the control group that did not show any tissue change.